Quantitative assessment of investment security risk in "21st Century Maritime Silk Road" countries - MA Fengyuan, GE Shanshan, ZHANG Ren, WANG Yizhi (Zhihui kongzhi yu fangzhen)
The "21st Century Maritime Silk Road" is a new trade road linking China and other countries in the world in the new era, promoting the development of Asia Pacific integration. With the increase of China’s investment in the "21st Century Maritime Silk Road" countries, its security is influenced by factors such as major country games, regional conflicts, and social instability, and also bringing great uncertainty to investment safety. Therefore, a reasonable assessment of investment security risk of the "21st Century Maritime Silk Road" is an important basis for ensuring investment security. In this paper, the investment security risk assessment index system is constructed comprehensively based on great power influence, state behavior and state interaction. Aiming at the uncertainty of the assessment index, hesitation degree distribution function of institution fuzzy set is established. The score function and distance measure of intuitionistic fuzzy set are improved, and the quantitative assessment model of investment security risk is constructed by combining TOPSIS method. The investment security risk in 27 countries along the "21st Century Maritime Silk Road" was experimentally verified, and the ranking was finally obtained based on different risk attitude of decision maker, which provided reference for the decision-making of the "21st Century Maritime Silk Road".